2008
DOI: 10.4161/cbt.7.7.6208
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling at methylated promoters in pancreatic adenocarcinoma

Abstract: Many genes undergo aberrant methylation in human cancers, and microarray platforms enable more comprehensive profiling of aberrant DNA methylation patterns.Results: 1,010 of 87,922 probes on the 88 K promoter array (606 genes) had a higher signal (log 2 > 2) in the pancreatic cancer line, Panc-1 compared to the non-neoplastic pancreatic duct line, HPDE. Using this cut-off, bisulfite sequencing and/ or MSP confirmed differential methylation of all 27 genes (66 probes) predicted to be methylated by the MCA array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 36 publications
4
129
0
1
Order By: Relevance
“…Previous studies have shown extensive epigenetic silencing of one or several of the miR-9 genes in cancer (Lehmann et al, 2008;Lujambio et al, 2008;Omura et al, 2008;Bandres et al, 2009;Hsu et al, 2009). This silencing was common in tumor tissue, whereas nearly absent in normal tissue.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have shown extensive epigenetic silencing of one or several of the miR-9 genes in cancer (Lehmann et al, 2008;Lujambio et al, 2008;Omura et al, 2008;Bandres et al, 2009;Hsu et al, 2009). This silencing was common in tumor tissue, whereas nearly absent in normal tissue.…”
Section: Discussionmentioning
confidence: 89%
“…This silencing was common in tumor tissue, whereas nearly absent in normal tissue. For example, in pancreatic adenocarcinoma, miR-9-1 was found to be methylated Hsa-miR-9 methylation and renal cell carcinoma MAT Hildebrandt et al in 89% of the tumor samples, but only 15% of the normal tissues (Omura et al, 2008). Furthermore, methylation of lysine residues 9 and 27 of histone H3, hallmarks of epigenetic gene silencing, was associated with miR-9-3 when gene expression was suppressed in breast cancer (Hsu et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hsa-miR-9 has been described as a putative tumor suppressor gene in recurrent ovarian cancer 31 and genome-wide profiling of methylated promoters identified hsa-miR-9-1 as a miRNA frequently hypermethylated in pancreatic adenocarcinoma. 32 Lehmann et al 33 showed differential methylation of hsa-miR-9-1 in a large series of primary human breast cancer specimens. In agreement with our results a good correlation between hypermethylation of the hsa-miR-9-1 gene and downregulation of expression in tumor tissue was found.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Altered miR-9 expression is associated with the development and progression of cancers, [22][23][24][25] Kaplan-Meier analysis of overall survival in patients with osteosarcoma, stratified according to median serum microRNA-9 (miR-9) concentration (expression). The colour version of this figure is available at: http://imr.sagepub.com nonsmall-cell lung cancer 16 ) highly expressed miR-9 promotes cancer-cell growth and/or metastasis.…”
Section: Discussionmentioning
confidence: 99%